Hirschsprung Disease: The Role of the Clinical Nurse Specialist - Julie-Ann Milbery; Joe Curry (MDPI AG, 2024)
Hirschsprung disease is a life-long condition that can have a significant impact on both children and their families. This article explores the role of the clinical nurse specialist and the support they can provide from initial diagnosis through the patient's surgical journey and right through to transition into adult services. Through the provision of education, training, signposting of social and psychological support, and linking in with community-based services, the clinical nurse specialist can help the child and family to limit that impact of the disease.